2014
DOI: 10.1002/adma.201403626
|View full text |Cite
|
Sign up to set email alerts
|

A Thermoresponsive and Magnetic Colloid for 3D Cell Expansion and Reconfiguration

Abstract: A dual thermoresponsive and magnetic colloidal gel matrix is described for enhanced stem‐cell culture. The combined properties of the material allow enzyme‐free passaging and expansion of mesenchymal stem cells, as well as isolation of cells postculture by the simple process of lowering the temperature and applying an external magnetic field. The colloidal gel can be reconfigured with thermal and magnetic stimuli to allow patterning of cells in discrete zones and to control movement of cells within the porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…The longer-term culture experiments thus demonstrated that the surfaces were able to function as 'reversible attachment' cell support matrices over timescales generally used for cell expansion. The utility of switchable attachment to polymer surfaces for cell culture has been extensively tested over recent years, 31,32 but the ability to culture cells at lower temperature and then release the cells by heating to body temperature may offer advantages for more thermally sensitive cell types. Overall, these results are significant also because they demonstrate a mechanism underlying the cell adhesion phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…The longer-term culture experiments thus demonstrated that the surfaces were able to function as 'reversible attachment' cell support matrices over timescales generally used for cell expansion. The utility of switchable attachment to polymer surfaces for cell culture has been extensively tested over recent years, 31,32 but the ability to culture cells at lower temperature and then release the cells by heating to body temperature may offer advantages for more thermally sensitive cell types. Overall, these results are significant also because they demonstrate a mechanism underlying the cell adhesion phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, thermo-responsive surfaces 7,8 have been used as supports for mammalian cell culture, as their changes in physicochemical properties at upper or lower critical solution temperatures (UCST, LCST) can facilitate cell detachment without the need for enzymatic passaging. [9][10][11][12][13] PNIPAM is the most commonly used thermo-responsive polymer, however, the presence of strong hydrogen bond donors and hydrogen acceptors in its structure can lead to inter-and intra-chain association entanglement. 14 By comparison, PEG-based polymers have a reversible phase transition that occurs without chain entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data had shown that PDEGMA adsorbed onto polystyrene-DVB microparticles with magnetic cores did not lead to any cytotoxicity in fibroblasts or stem cells. 18 Cell adhesion, distribution, viability and proliferation were thus evaluated. The thermoreversible fluid-to-gel transition of the colloidal gels allowed easy cell seeding when the gels were in their 10 | J.…”
Section: Application Of Thermoresponsive Magnetic Colloidal Gels To 3mentioning
confidence: 99%
“…18 Diethyleneglycolmethaacrylate (11 g, 59 mmol) was weighed into a round bottom flask and 1-dodecanethiol (0.08 g, 0.4 mmol) and 20 ml of 2-butanone were added. AIBN (0.07 g, 0.4 mmol) was added and the mixture was degassed with nitrogen for 25 minutes.…”
Section: Synthesis Of Linear Thermoresponsive 'Control' Polymermentioning
confidence: 99%
See 1 more Smart Citation